Electronic resources access: An academic library perspective - Mohammed Ali, Salihin (Institutional Knowledge at Singapore Management University, 2018)
The presentation highlights the role academic libraries play to provide access to online electronic resources to support teaching, learning and research. It includes findings from a recent trial of OpenAthens, an identity and access management solution for electronic resources.